PENGARUH PENGEMBANGAN KARIR, KOMPENSASI, DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS SOSIAL PROVINSI SUMATERA UTARA - Malau, Silvia Handayani; br Purba, Erika Apriani; Fitriano, Andre; br Harahap, Julienda (JURNAL LENTERA BISNIS, 2026)
The main objective of this study is to determine how promotion opportunities, salary levels, and workload affect the productivity of employees at the North Sumatra Provincial Social Service. This research will be conducted at the North Sumatra Provincial Social Service, located at Jl. Sampul No. 138, Sei Putih Barat, Medan Petisah District, Medan City, North Sumatra. The study population consists of seventy-eight individuals working at the North Sumatra Provincial Social Service as Civil Doctor Assistants (APN). This study used a saturated sample of 78 APN staff, selected using a non-probability sampling method. This study employed a Likert scale. The methods used to analyze the data included the coefficient of determination test, multiple linear regression, classical assumptions, and hypothesis testing. The results indicate that promotion opportunities, salary levels, and workload have a moderating effect on employee productivity at the North Sumatra Provincial Social Service. The North Sumatra Provincial Social Service considers promotion opportunities, salary levels, and workload in evaluating employee performance.